Literatur Review: The Role of Nutrition Education in Sports - Widya Astuti (Universitas Pendidikan Indonesia, 2020)
The low level of nutritional knowledge among athletes and coaches in Indonesia is on of the main problems. Therefore, it is important to know the role of nutrition education on improvment in knowledge, attitudes, and behavior and factors which affect the nutritional knowledge of the subject. Narrative review literature has a more flexible structure. The search for the source of article was carried out using Google Scholar, Pubmed, and Elsevier using the key terms: “education” “requirement”, “nutrition status”, “nutrition”, and “athletes”. Increased knowledge, attitudes, and behavior can apply consumption patterns that can meet nutritional needs as an athlete and for coaches, officials, and administrators can provide encouragement as a peer group in implementing balanced nutrition patterns in athletes' daily lives.